How the West brought war to Ukraine understanding how U.S. and NATO policies led to crisis, war, and the risk of nuclear catastrophe - Abelow, Benjamin (Siland Press, 2022)
This book explains the causes and recent historical events (during the 1990s and the 21st century) causing the crisis and war in Ukraine. It includes a discussion of how these events put the world at risk of nuclear war. It also touches on some general theory relevant to political science and international relations.--Publisher